KETAHANAN BERMUKIM MASYARAKAT KAWASAN RAWAN BENCANA (KRB) III GUNUNG MERAPI - , NUR HIDAYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Settlement is one of the basic human needs. Settlement areas generally have certain characteristics. Merapi Volcano is one of the most active volcano in the world. Some of its teritory are in the disaster prone area, so they do not fit for habitation. In fact many people are living in the slopes of Merapi. Post eruption of Merapi 2010 the local government attempted to relocate residents who reside in the prone-areas. Howewer three of nine villages where i the prone areas rejected the scenario. This research was done in three villages which reject the relocation program. These three villages are Srunen, Kalitengah Kidul and Kalitengah Lor. There are two purrposes of the research. The first is to describe the resilience settled of community in disaster prone areas. The second is to determine the factors that influence the resilience settled of community in disater prone areas. The method of this research is inductive qualitative with descriptive analysis. This research used phenomenological approach, which tried to interpret and make sense of the phenomena that found in the field. Finally, the synthesis process tried to make abstration in a concept. Result and conclusion of this research can be abstracted in the concept of \"ayem tentrem: urip nyanding Merapi\" it mean that living a calm, peaceful with everything completely guaranteed (secure) including livelihood, socio-cultural circumstances, the relationship with the natural environment and most importantly comfortable feeling which associated with the psychology condition of community. \"Nyanding Merapi\" means coexisting with Merapi, Merapi is considered not as an opponent but a comrade. Resilience settled of communities in disaster prone area covers economic resilience, social resilience and environmental resilience (disasters) in which strongly associated with the local wisdom. Merapi society is able to coexist with nature and able to survive in disaster prone areas. Factors that influence the resilience settled of community in disaster prone areas are the hometown factors. This factors include the origin livelihood, livable area, homeland hereditary guarded, spirit and comfort of live. Strong Pattern of rural and bond with nature is difficult to be changed. Livelihood resources related to their occupation as cattleman and farmer. Strong Pattern of rural, bond with nature, livelihood resources and their assets in hometown have pushed people to survive settled in disaster prone areas.